CASE REPORT ON TWO CONSECUTIVE PATIENTS WITH NEUROINVASIVE WEST NILE VIRUS INFECTION IN AN INTENSIVE CARE UNIT - Silviya Stoyanova; Raynichka Mihaylova-Garnizova; Emilia Naseva; Severina Dakova; Iva Christova; Konstantin Ramshev (Problems of Infectious and Parasitic Diseases)
We present the clinical course, and treatment of two consecutive cases of neuroinvasive West Nile virus (WNV) infection in the Clinic of Intensive Care, an Intensive Care Unit (ICU) at the Military Medical Academy - Sofia. Clinical and epidemiological data, microbiological, laboratory, molecular methods, and imaging techniques were used. Both patients resided in Sofia, Bulgaria, and had not travelled in recent months. The first case was a 60-year-old man who have had mental status changes, fever, and progression of existing Parkinson's disease. Antibodies to WNV were present in cerebrospinal fluid (CSF). His condition worsened with the development of sepsis and respiratory failure and he ended up lethally. The second case was a 72-year-old man who had fever and lower dyspeptic syndrome for one week, mental status changes, with adynamia to inability to walk independently, and head, hand and tongue tremors. CSF analysis showed mild pleocytosis with proteinorachy. Antibodies to WNV were present in serum, and PCR for WNV in urine was positive. The patient was admitted to ICU due to worsened mental and neurological status, coma and development of acute respiratory failure, necessitating intubation and assisted pulmonary ventilation. The patient ended lethally 13 days later. Neuroinvasive WNV infection can cause substantial morbidity, particularly among older adults, and high mortality, in the presence of comorbidities. Physicians should include West Nile virus infection in the differential diagnosis of aseptic meningitis and encephalitis, should perform appropriate laboratory tests, and report immediately the cases to the public health authorities.